Cognitive-Behavioral Psychoeducational Community Music Therapy for Enhancing Students’ Learning Motivation - Situmorang, Dominikus David Biondi (Buletin Konseling Inovatif, 2025)
Motivation is an important determinant for students’ academic achievement; however, many pupils report that their learning motivation decreases in particular prior to exams. Preventive steps, guidance and counseling teachers or school counselors reported lack of concentration, high anxiety, and low enthusiasm among high school students. This study investigated the utility of a Cognitive-Behavioral Psychoeducational Community Music Therapy Seminar/Workshop in improving students' motivation to learn before exams. A pre-experimental one-group pretest-posttest design was used with 213 senior high school students in Jakarta, Indonesia, aged between 15 to 18 years old. The Motivated Strategies for Learning Questionnaire (MSLQ) was employed to assess students’ motivation and learning strategies. The intervention, psychoeducation content using music therapy activities including group singing, rhythm-playing, and reflect. The paired-sample t-tests and effect size (Cohen’s d) was performed to data. Results revealed a highly significant elevation in overall motivation (Pretest M = 4.21; Posttest M = 4.78; t (212) = 14.32, p < .001; Cohen’s d = 0.69). Results of subscale analyses indicated there were increases in intrinsic goal orientation, task value, self-efficacy, and metacognitive self-regulation while test anxiety was decreased. Findings endorse the feasibility of CoMT-based seminars to be utilized as effective strategic school interventions for enhancing motivation and examination readiness. The incorporation of music therapy into guidance and counseling programs offers one dynamic and empirically supported method to support academic resilience among teenage students.